Aksjologiczne problemy związane z najnowszą literaturą polską. Casus prozy Jakuba Żulczyka - Kulczycka, Dorota (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The author of the article proposes the thesis that contemporary Polish literature, in many instances that include the prose and screenplays of Jakub Żulczyk, does not merely diagnose a particular moral condition of Polish society, but also generates it. Pierre F. Bourdieu’s term „symbolic violence” aptly describes this process, which involves the creation of negative or pathological behaviours. What is particularly dangerous is an increasing vulgarization of literary language, which proceeds according to the principle of the vicious circle: the author is initially inspired by the language of the street, which he subsequently enriches with new vulgar expressions. Those are, in turn, incorporated in the language. The impact of this kind of literature on the readers appears to be consistent with processes recognized by psychology such as priming, modelling, and developing scripts. Although the article makes references to Jakub Żulczyk›s prose, the phenomena it describes are not restricted to Polish literature, but universal. What might interest foreign readers are the psychological consequences of reading popular novels which exhibit the features and tendencies on which the article focuses.